HUBUNGAN SELF-AWARENESS DENGAN DISIPLIN BELAJAR SISWA DI SEKOLAH - Putri, Ernita; Gusri Handayani, Puji; Netrawati; Dwi Febriani, Rahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the fact that there are students who have not yet implemented learning discipline optimally. One of the factors that influence learning discipline is self-awareness. This research aims to (1) describe the level of students' self-awareness, (2) describe the level of students' learning discipline, (3) test the relationship between self-awareness and students' discipline. This study uses a quantitative method with a descriptive correlational type. The sample of this study was 259 students in grades X, XI, and XII at SMA N 2 Lubuk Sikaping in the 2025/2026 academic year. This study used a proportional random sampling technique. Data collection in the study was carried out using self-awareness and learning discipline questionnaires that have been tested for validity using the Pearson Product Moment formula and reliability using Cronbach Alpha for self-awareness of 0.851 and learning discipline of 0.865. Data analysis used descriptive methods and Pearson Product Moment correlation analysis. The results of this study indicate that (1) self-awareness is in the moderate category with a percentage of 57%, and (2) student learning discipline is in the moderate category with a percentage of 59%, and (3) there is a significant positive relationship between self-awareness and student learning discipline at school. This means that the higher the self-awareness, the higher the learning discipline. Self-awareness has an important role in improving student learning discipline. Therefore, developing self-awareness through guidance and counseling services is expected to help improve student learning discipline at school.